2007
DOI: 10.1007/s00330-007-0711-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow edema-like lesions change in volume in the majority of patients with osteoarthritis; associations with clinical features

Abstract: Bone marrow edema-like lesions change in volume in the majority of patients with osteoarthritis; associations with clinical features Abstract It has been suggested that bone marrow edema-like (BME) lesions in the knee are associated with progression of osteoarthritis (OA). The purpose of our study in patients with OA was to evaluate prospectively changes of BME lesions over 2 years and their relationship with clinical features. Magnetic resonance (MR) images of the knee were obtained from 182 patients (20% mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 12 publications
8
110
4
1
Order By: Relevance
“…One such phenomenon is a bone marrow lesion (historically termed bone marrow edema), which presents as a highintensity, diffuse fluid signal within the epiphyses of the femur and tibia of many patients with knee OA (19,20). A bone marrow lesion is identified by increased signal on fat-suppressed, T2-weighted scans, with lower signal contrast to background in T1-weighted scans of the same subchondral bone marrow region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such phenomenon is a bone marrow lesion (historically termed bone marrow edema), which presents as a highintensity, diffuse fluid signal within the epiphyses of the femur and tibia of many patients with knee OA (19,20). A bone marrow lesion is identified by increased signal on fat-suppressed, T2-weighted scans, with lower signal contrast to background in T1-weighted scans of the same subchondral bone marrow region.…”
Section: Discussionmentioning
confidence: 99%
“…The rat was placed supine in the MRI bed, and the right hind limb was extended and secured as described above. Using a flat surface-acquisition coil, we acquired images with anisotropic voxels with a resolution of 137 ϫ 137 ϫ 500 m. The MRI was operated in a fatsuppressed, spin-echo, T2-weighted scan mode specifically to visualize potential bone marrow lesion-like/edema-like phenomena in the tissue, as previously described (19,20). Each scan was ϳ15 minutes in duration.…”
Section: Methodsmentioning
confidence: 99%
“…They suggested that BMLs were associated with knee pain [15], could be predictive of progression [16] especially if they enlarged [17] or were associated with varus or valgus angulation [16]. Later reports, however, were less clear-cut even suggesting that BMLs were not only unassociated with Western Ontario and McMaster Universities index of OA scores (WOMAC™) [18,19] and other measures of patient symptoms but also fluctuated over a period of time, resolving and/or worsening with new lesions coming and going elsewhere in the same joint [20,21]. Again, these lesions did not correlate with patient symptoms.…”
Section: So Where Does the Problem Lie?mentioning
confidence: 99%
“…Two recent clues have emerged-firstly, that such lesions may progress to "cysts" [20,22] and also that at follow up progressive BMLs are associated with damage to overlying hyaline cartilage [23]. To understand these findings, it is timely to go back to some older literature.…”
Section: So Where Does the Problem Lie?mentioning
confidence: 99%
“…This presumably represents a sclerotic response to more focal stress/hyaline cartilage damage ogy findings in OA suggest that BML seen on MRI reflects metaplastic fibrovascular tissue in the bone marrow together with trabecular remodeling. However, most BML fluctuate in size over time, which may be observed after only a few months suggesting that BML reflect more active histopathological changes than structural remodeling [150][151][152][153][154][155]. In one of these reports, fluctuations in BML scores over 3 months were positively correlated with changes in urinary C-terminal crosslinking telopeptide of type II collagen, a biomarker reflecting cartilage turnover [150].…”
Section: Mri In Osteoarthritismentioning
confidence: 98%